Predicting Cover Crop Nitrogen Content with a Handheld Normalized Difference Vegetation Index Meter. Issue 1 (1st October 2019) - White, Charles M.; Bradley, Brosi; Finney, Denise M.; Kaye, Jason P.
Abstract : Core Ideas: Cover crop biomass N content (CC‐N) can be estimated in the field with a handheld NDVI meter. Separate calibration equations exist for different cover crop types in fall and spring. Rapidly estimating CC‐N could facilitate management of N‐related services provided by cover crops. Cover crop (CC) biomass nitrogen content (CC‐N; kg ha −1 ) is related to a number of ecosystem services but is rarely measured by farmers and agronomists because of the expense of sampling and analysis. We hypothesized that normalized difference vegetation index (NDVI) measured by a handheld meter could predict CC‐N. Using a dataset of 598 observations, we predicted fall biomass N with two separate calibrations for (i) clover‐type legumes and (ii) CCs consisting of brassicas ( Brassica spp.), cereal grasses, vining legumes, and grass–legume–brassica mixtures. Spring biomass N was predicted with three separate calibrations for (i) cereal grain CCs, (ii) brassicas, and (iii) CCs consisting of pure legumes and grass–legume–brassica mixtures. Quality of the calibrations ranged from r 2 = 0.72 to r 2 = 0.87. Rapidly and inexpensively estimating CC‐N with an NDVI meter could enhance the ability of farmers and agronomists to routinely monitor and manage the N‐related ecosystem services provided by CCs.